Running anatomy - Puleo, Joe; Milroy, Patrick (Champaign, IL Human Kinetics, 2019)
See how to improve your running strength, speed, and endurance with Running Anatomy, second edition. This new edition of the best-selling running guide delivers more exercises, more insight, and more illustrations to show you how to increase your muscle strength, optimize the efficiency of your running motion, and minimize your risk of injury. Running Anatomy features 48 of the most effective exercises for runners, each with clear step-by-step descriptions and full-color anatomical illustrations highlighting the muscles in action. Each illustration helps you better understand how muscles, ligaments, and tendons all work together as your body moves. Running Anatomy clearly links each exercise to running performance. You'll see how to strengthen specific muscles and improve gait efficiency for faster times and more fluid runs. Plus you'll learn how to eliminate anatomical imbalances that can lead to the most common injuries that runners face, including plantar fasciitis, lower-back pain, knee aches and strains, and torn muscles and tendons. Feel prepared for any challenge that comes your way. you'll find exercise variations to train for every condition and competition-for various terrains, speeds, elevations, and distances, from sprint to marathon. You'll also learn how new gear and technology-enhanced equipment can maximize your training and performance. Whether you're a fitness runner looking to conquer hills with more speed and strength or a competitive runner looking for extra edge in performance and finishing kick, Running Anatomy will ensure that you're ready to achieve your personal best
The runner in motion -- Training in concepts -- External factors that affect performance -- Feet and ankles -- Legs -- Core -- Shoulders and arms -- Chest and back -- Injury prevention -- Alternative training activities -- Gear and advancement
Keywords: Running -- Physiological aspects; Running -- Training; Running injuries -- Prevention